2017
DOI: 10.3349/ymj.2017.58.3.626
|View full text |Cite
|
Sign up to set email alerts
|

The Need for New Donor Stratification to Predict Graft Survival in Deceased Donor Kidney Transplantation

Abstract: PurposeThe aim of this study was to determine whether stratification of deceased donors by the United Network for Organ Sharing (UNOS) criteria negatively impacts graft survival.Materials and MethodsWe retrospectively reviewed deceased donor and recipient pretransplant variables of kidney transplantations that occurred between February 1995 and December 2009. We compared clinical outcomes between standard criteria donors (SCDs) and expanded criteria donors (ECDs).ResultsThe deceased donors consisted of 369 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…They might be influenced by different factors including recipients' and donors' age, CIT, HLA mismatch and dialysis vintage [26,27]. A major concern of the ESP was, therefore, that elderly recipients not only have to cope with the effects of their own age, but also experience disadvantages from the elderly graft as recipients' and donors' age has been shown to be a risk factor for death, perioperative and peri-transplantation complications [28][29][30][31][32][33][34]. Heldal et al more specifically identified donors' age �60 years as a predictor for increased mortality and graft loss in the elderly [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They might be influenced by different factors including recipients' and donors' age, CIT, HLA mismatch and dialysis vintage [26,27]. A major concern of the ESP was, therefore, that elderly recipients not only have to cope with the effects of their own age, but also experience disadvantages from the elderly graft as recipients' and donors' age has been shown to be a risk factor for death, perioperative and peri-transplantation complications [28][29][30][31][32][33][34]. Heldal et al more specifically identified donors' age �60 years as a predictor for increased mortality and graft loss in the elderly [35].…”
Section: Discussionmentioning
confidence: 99%
“…Graft function and survival are influenced by the dialysis vintage and the associated comorbidities [ 4 , 19 , 29 , 30 , 32 , 33 , 39 ]. Quick transplantation of an ECD graft and shorter dialysis vintage seem to outweigh the benefits of a younger graft despite a longer dialysis vintage [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em todo o transcurso até a doação efetiva outras questões éticas podem surgir, dentre elas o questionamento a respeito do destino do órgão ou da identidade dos familiares do doador, seja por curiosidade, desejo de expressar gratidão ou até mesmo como forma de ter ao alcance uma parte do ente querido; essa constitui uma situação que exige ética por parte do profissional que precisa manter sigilo, visto o perigo que tal informação possa representar para o cotidiano de uma ou de ambas as partes. Como a autorização familiar é prevista em lei, outra questão que se enquadra nos preceitos éticos é a não retirada de órgãos em pacientes sem identificação, uma vez que, se a família não puder autorizar, o processo não ocorre (18) .…”
Section: Interferências No Processo De Transplantes De óRgãos E Tecidosunclassified
“…The severe shortage of organs available for standard transplantation has led to an increase in living-donor kidney transplants on the one hand, and increased acceptance of marginal donor organs on the other. Feasible marginal donor strategies include the use of double-kidney transplants, including organs from elderly donors with an already reduced renal function [8,9], or the transplantation of organs derived from expanded criteria donors (ECDs) [1012]. In addition, the transplantation of organs from donors with a history of acute kidney injury (AKI) is also possible, and is increasingly utilized [13].…”
Section: Introductionmentioning
confidence: 99%